Robot bípedo para ayuda en el aprendizaje de matemáticas en niños de quinto año de educación básica - Centeno Guaman , Holger Marvin (2024)
The integration of robotics into primary education represents a promising innovation within the Ecuadorian context, where traditional methods for teaching mathematics often face challenges in motivating students and fostering comprehension of core concepts. This project focused on designing and implementing an interactive bipedal robot as a pedagogical tool for fifth-grade students, aiming to enhance mathematics education through human-robot interaction. The methodology included a literature review, interviews with teachers and robotics experts, and pilot testing with students. Results indicated that the robot successfully captured students’ attention and encouraged active participation, improving understanding of basic concepts. Additionally, technical and pedagogical challenges were identified, such as curriculum integration and robot maintenance. In conclusion, the bipedal robot not only showed potential to transform classroom learning but also highlighted the need for a contextualized and adaptable approach to meet the country’s educational needs and ensure successful implementation.